2022
DOI: 10.1002/advs.202201294
|View full text |Cite
|
Sign up to set email alerts
|

Protein Scaffold‐Based Multimerization of Soluble ACE2 Efficiently Blocks SARS‐CoV‐2 Infection In Vitro and In Vivo

Abstract: Soluble ACE2 (sACE2) decoys are promising agents to inhibit SARS‐CoV‐2, as their efficiency is unlikely to be affected by escape mutations. However, their success is limited by their relatively poor potency. To address this challenge, multimeric sACE2 consisting of SunTag or MoonTag systems is developed. These systems are extremely effective in neutralizing SARS‐CoV‐2 in pseudoviral systems and in clinical isolates, perform better than the dimeric or trimeric sACE2, and exhibit greater than 100‐fold neutraliza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…At 10 dpi, 7 of the ten animals in the control group had significant weight loss (> 25%) and were euthanized in the final days of the experiment because three mice in this group were dying. Vaccinated animals completed the experiment without losing weight 29 . 12 days after the challenge, lung tissues of all animals were harvested at necropsy and analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…At 10 dpi, 7 of the ten animals in the control group had significant weight loss (> 25%) and were euthanized in the final days of the experiment because three mice in this group were dying. Vaccinated animals completed the experiment without losing weight 29 . 12 days after the challenge, lung tissues of all animals were harvested at necropsy and analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…This encouraged experts to produce a stable mutant dimeric and a homo-trimeric variant of sACE2 with preserved peptidase activity but higher binding affinity to RBD (about 600 pM for the dimeric and 60 pM for the trimeric sACE2) to hinder mACE2-RBD complexification [ 257 , 259 ]. In order to block S proteins on each SARS-CoV-2 particle with high efficiency, multimerized sACE2-fusion proteins have been manufactured through molecular engineering [ 260 ].…”
Section: Sace2: Increasing Sars-cov-2 Infectivity?mentioning
confidence: 99%
“…In the treated group, histological examination of lung tissues revealed healing and restoration of normal tissue components (Figure 3C). [35][36][37] Lung sections were analyzed after staining with hematoxylin and eosin and lung inflammation was semi-quantitatively scored between 0 and 3 (0: no inflammation, 1: low, 2: medium, 3: high). Control mice exhibited significantly higher histopathology scores than extract treated mice.…”
Section: In Vivo Experiments With S Lappa Extractsmentioning
confidence: 99%
“…Only one of the 10 animals in the treated group given S. lappa extract showed this condition (Figure 3B). [34][35][36][37] One out of 10 animals in the group 1 that was treated with S. lappa extract developed disease at 9 dpi, while nine animals (90%) were completely healthy and survived until the end of the experiment. Gross pathology showed that most of the lungs in the control group had pneumonic and hyperemic areas, while the lungs in the treated group were clean and showed no signs of infection.…”
Section: In Vivo Experiments With S Lappa Extractsmentioning
confidence: 99%